Розвиток сільськогосподарської кооперації на Волині у 1920-х роках - Власюк, Ігор; Vlasiuk, Ihor (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено розвиток сільськогосподарської кооперації у Волинській губернії (пізніше – окрузі, у складі СРСР) протягом 1920-х років, успіхи та проблеми діяльності кооперативів різних видів.

The development of agricultural co-operation of soviet Volyn during 1920th, the successes and the problems of activity of the cooperative stores is explored in the article. Agricultural co-operation developed under influencing and direct control from the side of public organs. The co-operators gradually ousted a private capital at the market. Successes in their activity it was been: multiplying the amount of the associations and the members; profitability of cooperative stores of hop-growers; the examples of successful economic activity of separate associations of consumers. The problems in the development of co-operation were related to absence of the proper experience, financial resources and desire of certain part of peasantry to be the members of co-operative societies. In the conditions of introduction of policy of collectivization was administrative pressure from the side of the state on development of co-operation and insufficient sponsorship on a mud flow.
The Development of Agricultural Co-Operation of Volyn in 1920th
Keywords: сільськогосподарська кооперація; Волинь; нова економічна політика; селянство; радянська влада; agricultural co-operation; Volyn; new economic policy; peasantry; soviet power